1999
DOI: 10.1302/0301-620x.81b5.9374
|View full text |Cite
|
Sign up to set email alerts
|

Shock-wave therapy is effective for chronic calcifying tendinitis of the shoulder

Abstract: We report a prospective study of the effects of extracorporeal shock-wave therapy in 195 patients with chronic calcifying tendinitis. In part A 80 patients with chronic symptoms were randomly assigned to a control and three subgroups which had different treatment by low-energy and high-energy shock waves. In part B 115 patients had either one or two high-energy sessions. We recorded subjective, functional and radiological findings at six months after treatment. The results showed energy-dependent success, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(80 citation statements)
references
References 0 publications
1
69
0
3
Order By: Relevance
“…9,10,17,18 In cases of ESWT, the elimination rate was also wide, with 15% to 70%, even though the rate of disintegration and resorption increased with higher levels of shock waves and longer periods of follow-up. 14,[22][23][24]29,33 On the other hand, in our previous study on arthroscopic treatment of calcific tendinitis, the deposits were completely removed in 72% of the shoulders studied. 21 In the present study, we observed that type I and type II deposits by the classification of Gartner and Simons changed to type II and type III over time in most of the shoulders.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…9,10,17,18 In cases of ESWT, the elimination rate was also wide, with 15% to 70%, even though the rate of disintegration and resorption increased with higher levels of shock waves and longer periods of follow-up. 14,[22][23][24]29,33 On the other hand, in our previous study on arthroscopic treatment of calcific tendinitis, the deposits were completely removed in 72% of the shoulders studied. 21 In the present study, we observed that type I and type II deposits by the classification of Gartner and Simons changed to type II and type III over time in most of the shoulders.…”
Section: Discussionmentioning
confidence: 91%
“…NSAIDs therapy has been the main conservative method. Other methods include steroid injection, mild shoulder passive stretching exercises, ESWT, 14,15,24 and needle aspiration and lavage. We applied various conservative methods suitable to each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following investigators described calcifying tendinopathy as calcium deposits in necrotic collagen tissue (Tashjian et al 2009). Therefore, the application of shockwave therapy in calcified tendon induces an increased pressure within the therapeutic focus, causing fragmentation and cavitation inside the amorphic calcifications, leading to disorganisation and disintegration of these deposits (Loew et al 1999). This effect does not occur when there is lamellar bone organized in osteons in the target zone because there is too little space to generate cavitation (Russo et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although more attention has been recently paid to ESWT, long-term results with the noninvasive treatment are currently no better than with surgery [21][22][23][24].…”
Section: Extracorporal Shockwave Therapymentioning
confidence: 99%